SIMILARITIES AND DIFFERENCES OF TYPES OF VOICE IN ENGLISH AND UZBEK LANGUAGES - Qiyomova Sevara Erkinjon qizi, Muhammedov Aziz Shavkatovich, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
The aim of the article is to set out the need for studying passive and active voices in English and Uzbek, as well as their translation from English into Uzbek. In English and Uzbek language, the aim of this Article is to present an overall classification of parts of speech, which are used as passive or active voices.